DEVELOPING ENGINEERING EDUCATION FOR A GLOBAL COMMUNITY - Vasily G. Ivanov; Yury P. Pokholkov; Alla A. Kaybiyaynen; Julia N. Ziyatdinova (Высшее образование в России)
The paper describes the trends of engineering education development, innovations and the best experiences of the world universities in training engineers, discussed at the eighth World Engineering Education Forum WEEF 2014 in Dubai. A special focus is given to the trends and experience in the Russian universities in training engineering educators and their professional development, globalization, internationalization of engineering education, problems of digital learning, training engineers for science intensive power engineering of the future.